2022
DOI: 10.1186/s12883-022-02826-8
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the incidence of stroke-associated pneumonia: an evidence-based practice

Abstract: Background Pulmonary infection is a frequent complication among stroke patients and adversely affects clinical outcomes, increases the length of hospitalization stay and costs, and aggravates the financial burden of the national medical health system. Early identification and management of high-risk patients are necessary and imperative to reduce the incidence of stroke-associated pneumonia (SAP). Aim The evidence-based practice project evaluated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…Higher oral bacterial counts are found [ 35 , 36 ], gram negative and anaerobic organisms are increasingly present in the microbiome, and the nature of any infection may change [ 37 ]. Studies have shown that, for those most at risk, effective proactive mouth care can mitigate any risk [ 38 , 39 ]. Poor oral health and oral frailty are associated with an increased mortality and morbidity [ 40 ].…”
Section: Frailty and Oral Frailtymentioning
confidence: 99%
“…Higher oral bacterial counts are found [ 35 , 36 ], gram negative and anaerobic organisms are increasingly present in the microbiome, and the nature of any infection may change [ 37 ]. Studies have shown that, for those most at risk, effective proactive mouth care can mitigate any risk [ 38 , 39 ]. Poor oral health and oral frailty are associated with an increased mortality and morbidity [ 40 ].…”
Section: Frailty and Oral Frailtymentioning
confidence: 99%
“…In addition, except preventive antibiotics, lots of other intervention could prevent SAP in patients with stroke of high risk. For instance, dysphagia assessment and management ( 52 ), modes of nutritional support ( 53 , 54 ) and care programme ( 55 ) also play important parts in the prevention of SAP.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first meta-analysis with trial sequential analysis to investigate the preventive effect of the patient's care bundle on SAP in stroke patients. Pooled (22). Evidence-based protocol initiated by nurses for syndrome management is scientific, effective, targeted, safe, and systematic in stroke units (53).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Turner et al ( 21 ) discovered that achieving a care bundle for ischemic stroke could significantly reduce the occurrence of SAP. It should be noted that the majority of currently available care strategies are single or multiple preventive interventions that are not evidence-based ( 22 ). Evidence-based protocol initiated by nurses for syndrome management is scientific, effective, targeted, safe, and systematic in stroke units ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation